Analysis of quality measure that quality-relevant of bakery products - Halchenko, Y. M.; Kavunenko, E. R. (НТУ ДП, 2022)
Introduction. Bakery products are the main food products, which are in the first group (Food products for mass consumption) in the systematization of the main types of food products according to their purpose. Ukraine produces a lot of bakery products, the number of different products related to bakery products exceeds 300. Bakery products include such products as: various types of loaves and bread, braids, bagels, rolls, etc. In this paper, we will consider the example of making a loaf "cut". According to DSTU-P 4587: 2006 "Loaf" "sliced" consists of: wheat flour of the highest grade, prepared drinking water, baking yeast, table salt, white crystalline sugar, skimmed milk powder, table margarine "Special milk" 82% fat (sunflower oil) , drinking water, salt) [1]. As a rule, the main technological processes of bakery production are mechanized. Consider the production of loaf and the processes that accompany it. Description of the technological process and the choice of controlled parameters.
Keywords: хлебобулочные изделия; продукты питания